Interferensi dalam Cerpen Siswa SMP Negeri 2 Merbau Mataram Kabupaten Lampung Selatan - Ratih Rahayu (Kantor Bahasa Provinsi Maluku Utara, 2017)
This research investigates the interference which exist in short stories written by the students of SMPN 2 Merbau Mataram, South Lampung Selatan. The problems investigated are the kinds of interference existing in the short stories and the factors which couse the interference in these short stories. The use of Indonesian in the short stories is the fact mixed with foreign languages (English), slang word, local languages. This interference occurs in morphological, lexical, and syntactical levels. From 40 short stories being investigated, there are 35 short stories in which the case of interference. There are only 5 short stories in which the case of interferences is not found. In these numbers are made into percentage, in total the percentage of short stories containing interference is 87,5% and the ones which are do not contain the interference is 12,5%. The interference is caused by some factors, they are: the bilingualism of the student, boredom, prestige, avoiding unnatural phrases, the vocabularies are considered shorter compared to their equivalents in Indonesian, and the vocabularies do not have equivalents in Indonesia.